First report on atrazine monitoring in drinking water from Ijebu-North, South-West Nigeria: Human health risk evaluation and reproductive toxicity studies - Owagboriaye, Folarin; Oladunjoye, Rasheed; Adekunle, Oladunni; Adeleke, Mistura; Salisu, Titilola; Adenekan, Adedamola; Sulaimon, Abibat; Dedeke, Gabriel; Lawal, Olusegun (Frontiers in Toxicology, 2022)
There are no available data on the level of atrazine in drinking water from rural agricultural areas in Nigeria and its potential health implications. Here, we measured atrazine residue in 69 hand-dug wells (HDW), 40 boreholes (BH), and 4 major streams from the 6 communities (Ago-Iwoye, Ijebu-Igbo, Oru, Awa, Ilaporu, and Mamu) in Ijebu North Local Government Area, Southwest Nigeria. Values of atrazine obtained were further used for the evaluation of non-carcinogenic risk associated with ingestion and dermal contact in adults and children as well as reproductive toxicity evaluation. A total of 41 HDW, 22 BH, and the 4 streams showed varying concentrations of atrazine, which was higher in HDW than BH and stream. Ago-Iwoye recorded the highest concentration of 0.08 mg/L in its HDW while the lowest concentration of 0.01 mg/L was recorded in HDW from Oru. Although the Hazard Index (HI) values associated with ingestion and dermal contact for children were higher than in adults, the values were below the acceptable limit for all the communities. Significant (p < 0.05) alterations in the oxidative stress parameters, reproductive hormones, sperm parameters, and mild testicular lesions were only observed in rats exposed to atrazine at 0.08 mg/L compared to control. But atrazine at 0.01, 0.03, and 0.04 mg/L triggered a defence mechanism capable of protecting the structural integrity of the testes and preventing reproductive dysfunction.